Analysis of emotional self-regulation in toddlers and preschoolers (interactive group II) in the GAM-Guanacaste transition program during the "Aprendo en casa" strategy due to COVID-19 - Solís Solís, Delia María (2023)
During 2020, as a result of the global COVID-19 outbreak, sanitary measures were taken in Costa Rica to prevent the spread, including lockdown. Therefore, the Ministry of Public Education established the "Aprendo en casa" strategy so that the learning process suffered less affectation. The research was carried out with the toddlers and preschoolers of the Maternal and Preschool programs (interactive II) and Transition cycles GAM-Guanacaste, as well as the teachers and legal caregivers of this population. The family environment of each student, their learning environments, and emotional self-regulation practices were analyzed during the COVID-19 outbreak new reality. Because the research is within the positivist paradigm and the quantitative approach, the information collected was analyzed through statistical data. It determined that the analysis of patterns in the behavior of the early childhood student, as well as establishing some causes or crises, such as changes in eating habits, sleep routines, irritability, and anxiety, among others. It allowed us to visualize the effects of the lockdown at a pedagogical-emotional level in early childhood learners due to the pandemic. The possibilities of socializing, recreation spaces, and outdoor activities were reduced, and they stopped sharing with other family members and/or participating in celebrations.